Alpha Synuclein only Forms Fibrils In Vitro when Larger than its Critical Size of 70 Monomers. (24th August 2021) - Sanchez, Santiago Enrique; Whiten, Daniel R.; Meisl, Georg; Ruggeri, Francesco Simone; Hidari, Eric; Klenerman, David
Abstract: The aggregation of α‐synuclein into small soluble aggregates and then fibrils is important in the development and spreading of aggregates through the brain in Parkinson's disease. Fibrillar aggregates can grow by monomer addition and then break into fragments that could spread into neighboring cells. The rate constants for fibril elongation and fragmentation have been measured but it is not known how large an aggregate needs to be before fibril formation is thermodynamically favorable. This critical size is an important parameter controlling at what stage in an aggregation reaction fibrils can form and replicate. We determined this value to be approximately 70 monomers using super‐resolution and atomic force microscopy imaging of individual α‐synuclein aggregates formed in solution over long time periods. This represents the minimum size for a stable α‐synuclein fibril and we hypothesis the formation of aggregates of this size in a cell represents a tipping point at which rapid replication occurs. Abstract : The critical size for α‐synuclein to form a stable fibrils, which can then replicate by monomer addition and fragmentation, has been found to be 70 monomers. Preventing aggregates from reaching this critical size would be a key cellular protective mechanism.